Biocomposites based on poly(lactic acid)/willow-fiber and their injection moulded microcellular foams - M. T. Zafar; N. Zarrinbakhsh; A. K. Mohanty; M. Misra; S. N. Maiti; A. K. Ghosh (eXPRESS Polymer Letters, 2016)
Natural fiber reinforced biocomposites have recently attracted many researchers because of their biodegradability, cost effectiveness and ecofriendliness. The present study investigates the properties of willow-fiber reinforced poly(lactic acid) based composites and their foam processability. Microcellular foams of the composites were prepared by foam injection moulding using nitrogen gas as the blowing agent. The effects of willow-fiber addition on the morphology, mechanical properties, thermal stability, crystallization, and heat deflection temperature (HDT) were studied. At 30 weight percent [wt%] willow-fiber content, unfoamed composites showed good improvement in specific tensile and flexural moduli. Addition of willow-fiber increased crystallinity and the rate of crystallization and yielded narrow crystallite size distribution as observed by differential scanning calorimetry (DSC). Scanning electron microscopy (SEM) results of the foamed composites revealed that increase in willow-fiber content caused smaller average cell size and higher cell density. Specific notch impact strength of foamed composites at both 20 and 30 wt% willow-fiber content showed increasing trend compared to that of their unfoamed counterparts.